2005
DOI: 10.1016/s0002-9440(10)62951-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophils in the Induction of Glomerulonephritis by Anti-Myeloperoxidase Antibodies

Abstract: In humans, circulating anti-neutrophil cytoplasm autoantibodies (ANCAs) with specificity for myeloperoxidase (MPO) are strongly associated with the development of pauci-immune necrotizing and crescentic glomerulonephritis (NCGN). In mice, we have demonstrated that intravenous injection of mouse antibodies specific for mouse MPO induces NCGN that closely mimics the human disease. We now report that the development of NCGN in this experimental model is accompanied by glomerular accumulation of neutrophils and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
202
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(211 citation statements)
references
References 30 publications
6
202
0
3
Order By: Relevance
“…Although the pathophysiological significance of these cells during atherogenesis has not yet been well documented, it is suggested that these cells are pro-atherogenic [73]. Neutrophils play a major role in the development of many forms of vasculitis [74,75]. In particular, MPO, an important enzyme from myeloid granules, has been implicated in the pathogenesis of atherosclerosis [76,77].…”
Section: Pathophysiology Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 99%
“…Although the pathophysiological significance of these cells during atherogenesis has not yet been well documented, it is suggested that these cells are pro-atherogenic [73]. Neutrophils play a major role in the development of many forms of vasculitis [74,75]. In particular, MPO, an important enzyme from myeloid granules, has been implicated in the pathogenesis of atherosclerosis [76,77].…”
Section: Pathophysiology Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 99%
“…PR3-and MPO-ANCA binding to their target antigens on the membrane of neutrophils and monocytes leads to cell activation (3,4). ANCA pathogenicity and the pivotal role of the ANCA-neutrophil interaction were established in several animal models (5)(6)(7)(8)(9). In contrast to MPO, membrane-PR3 (mPR3) has a bimodal expression pattern resulting in distinct mPR3 low and mPR3 high subsets.…”
mentioning
confidence: 99%
“…Recently, the passive transfer of anti-MPO mAb from MPO-deficient mice into wild-type mice resulted in systemic vasculitis, and the clinical manifestations included necrotizing pauciimmune glomerulonephritis (25). Moreover, neutrophil depletion completely prevented this disease in another mouse model, thus firmly establishing the role of ANCAs and neutrophils in the induction of vasculitis (12). The findings from animal models regarding PR3-specific ANCAs are currently less clear, although in one mouse model, anti-PR3 antibodies accelerated TNF␣-mediated dermal inflammation (26).…”
Section: Discussionmentioning
confidence: 94%
“…The ANCA-activated neutrophils generate reactive oxygen species and release tissue-toxic granule proteins, both of which are functions that mediate endothelial cell damage and ultimately lead to vasculitis (3)(4)(5)(6)(7)(8)(9)(10)(11). Recently, the central role of neutrophils in the induction of ANCA-mediated vasculitis was shown by neutrophil depletion in a mouse model of glomerulonephritis (12). Investigations of the underlying signal transduction pathways that control this cytokine-mediated priming and ANCA-induced activation of neutrophils identified the participation of p38 MAPK, ERK, protein kinase C, Syk, p21 ras , and phosphatidylinositol 3-kinase (PI 3-kinase)/Akt (9,10,(13)(14)(15)(16).…”
mentioning
confidence: 99%